Arrugula—Eruca sativa Mill. - James M. Stephens (EDIS)
This document provides an overview of arugula (Eruca sativa Mill.), detailing its description, uses, cultivation, and harvesting. Arugula, also known as roquette, is a low-growing annual with spicy, pungent leaves used in salads and as a potherb. It thrives in cool seasons and is grown commercially and in home gardens in Florida. The plant matures in 2-3 months and requires minimal pest control. Harvesting involves picking young, tender leaves, which can be used fresh or cooked. The document emphasizes arugula's minor but notable presence in U.S. agriculture. Original publication date April 1994.